2021
DOI: 10.3390/ani11123353
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light Intensity, Strain, and Age on the Behavior, Jumping Frequency and Success, and Welfare of Egg-Strain Pullets Reared in Perchery Systems

Abstract: The effects of light intensity (L) are not well studied in pullets. Our research objective was to study the effect of L on navigational success, behavior, and welfare of two pullet strains (S). In two repeated trials, a 3 × 2 × 4 factorial arrangement tested three L (10, 30, 50 lux) and two S (Lohmann Brown-Lite (LB), LSL-Lite (LW)) at four ages. One thousand eight hundred pullets/S (0–16 wk) were randomly assigned to floor pens within light-tight rooms (three pens/S/room, four rooms/L) containing four paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…No other differences were found in the remaining wing and body kinematics despite strain differences being reported in the musculoskeletal system and behavior. Although similar in many aspects, many studies have found that white- and brown-feathered hens respond differently to the provision of equipment such as perches, more complex housing options (ramps, multiple tiers/platforms, and perches) and additional space for locomotion ( Kozak et al., 2016 ; Ali et al., 2019 ; Chew et al., 2021 ; Pufall et al., 2021 ; Garant et al., 2022 ). Even as pullets, white-feathered birds exhibit increased rates of locomotion, higher bone breaking strength of the tibiae and heavier pectoralis-to-body mass ratios when reared with more space and elevated equipment ( Chew et al., 2021 ; Pufall et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No other differences were found in the remaining wing and body kinematics despite strain differences being reported in the musculoskeletal system and behavior. Although similar in many aspects, many studies have found that white- and brown-feathered hens respond differently to the provision of equipment such as perches, more complex housing options (ramps, multiple tiers/platforms, and perches) and additional space for locomotion ( Kozak et al., 2016 ; Ali et al., 2019 ; Chew et al., 2021 ; Pufall et al., 2021 ; Garant et al., 2022 ). Even as pullets, white-feathered birds exhibit increased rates of locomotion, higher bone breaking strength of the tibiae and heavier pectoralis-to-body mass ratios when reared with more space and elevated equipment ( Chew et al., 2021 ; Pufall et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although similar in many aspects, many studies have found that white- and brown-feathered hens respond differently to the provision of equipment such as perches, more complex housing options (ramps, multiple tiers/platforms, and perches) and additional space for locomotion ( Kozak et al., 2016 ; Ali et al., 2019 ; Chew et al., 2021 ; Pufall et al., 2021 ; Garant et al., 2022 ). Even as pullets, white-feathered birds exhibit increased rates of locomotion, higher bone breaking strength of the tibiae and heavier pectoralis-to-body mass ratios when reared with more space and elevated equipment ( Chew et al., 2021 ; Pufall et al., 2021 ). Taken together, these studies indicate that white-feathered strains benefit and respond more positively to rearing in more complex environments, while little effect is seen in brown-feathered strains ( Pufall et al., 2021 ; Rentsch et al., 2023a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…All birds were cared for as specified in the Guide to the Care and the Use of Experimental Animals by the Canadian Council of Animal Care. The data collected for this paper was part of a larger project ( Chew et al, 2021a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…Light intensity may affect laying hen behaviors and production performance. For caged, laying hen production, the dominant light intensity (LI) regime is 20 lux in the early stage, 5-10 lux in the growing stage, and 10-15 lux in the laying period [52].With the concerns of behavior and welfare, a study revealed that pullets spent more time preening at 50 lux than at 10 lux, spent more time wall pecking at 10 lux than at 50 lux, and had higher jumping frequency at 30 lux than at 10 lux [60]. When exposed to extremely high LI (500 lux [61], 121.8 lux [62]), layers produced smaller eggs in size and total egg mass, which indicated inadequate feed intake under high LI conditions.…”
Section: Light Intensitymentioning
confidence: 99%